A combined rate-shaping-splitting injection strategy for regulating stratification characteristics of fuel sprays. (25th March 2021) - Ramezani, S.; Amani, E.; Saffar-Avval, M.
Highlights: A novel combined injection rate-shaping-splitting strategy is proposed. The connection between the penetration lengths and stratification is analyzed. The capability of the new strategy for stratification control is investigated. 50% increase in stratification, with unchanged vapor penetration, is achievable. The number of split injections and flow-rate coefficients are the key parameters. Abstract: Producing a desired level of fuel stratification has recently aroused much interest to improve performance of combustion systems. In the present work, an injection strategy is proposed by combining the rate-shaping (IRS) and split-injection approaches for regulating the level and quality of stratification. An Eulerian-Lagrangian numerical model is detailed and calibrated against available experiments to study the effect of the uniform and combined IRS-splitting strategy parameters on spray characteristics. The results are analyzed carefully to identify the connection between the liquid and vapor penetration lengths (LL and VL) and the stratification parameters. We also try to reveal the physics underlying the variation of these parameters by the change of common design variables, like the ambient temperature and pressure, as well as by the variables specific to the IRS-splitting strategy. It is proven that the stratification parameter is a better measure of mixture inhomogeneity than VL. For instance, the proposed combined strategy is able to achieve a 50% increase in stratification while keeping the VL variation limited to 3%. Finally, our results demonstrate that the stratification can be effectively controlled by the combined strategy by adjusting the number of split injections and flow-rate coefficients of the main and pilot injections.